Extracting lithium from a lithium aluminate complex by vacuum aluminothermic reduction - Di Y.Z.; Peng J.P.; Wang Y.W.; Feng N.X. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The molten salt electrolysis of LiCl‒KCl is presently the primary method of producing lithium, but it is costly and has environmental issues in addition to other disadvantages. Vacuum thermal reduction may be used extensively in the future because it offers low energy consumption, a high purity product and short cycle times. The present study investigated a novel process for the extraction of lithium from Li5AlO4 clinker by vacuum aluminothermic reduction. The Li5AlO4 clinker was prepared in ambient air using lithium hydroxide, alumina and calcium oxide. The results show that this process can proceed in conjunction with a lower ratio of raw materials to lithium (8.89:1) and provides lithium reduction rates in excess of 97%. In addition, the reduction slag consists mainly of 12CaO•7Al2O3, which can be used to produce aluminum hydroxide. Thus, this process represents a highly efficient and environmentally-friendly method of generating lithium.